Combinación de reguladores de crecimiento en la fase de enraizamiento in vitro de tres variedades de banano - Arévalo González, Wilson Alberto (2010)
In the laboratory of Biotechnology of the Faculty of Agricultural Sciences, he was carried out the rehearsal it has more than enough combination of regulators of growth in the take root phase in vitro of three banana tree varieties whose objectives were: 1. To determine the appropriate dose of the alone regulators of growth or in combination for the take root phase; 2. To settle down which variety presents the best answer to the means of cultivation in the take root phase; 3. To carry out the economic analysis of the treatments. Son was selected, of 1 m of height, considering vigor, production, sanity and active state. The extracted cormo of the son was washed with common water, it was eliminated the sheaths foliares, until achieving a size of 7 cm, locating the vegetative point; in the camera of flow to be laminated washed the material with sterilized distilled water and working under aseptic conditions the fabric was manipulated reducing the size of the explante, it was disinfected with chlorine and he washed himself with distilled water; until reaching 1 cm of longitude, and it was sowed in the means of cultivation; the utilized basal means was that of Murashige and Skoog (MS) suplementando with vitamins and hormones, activated carbon, macrónutrientes, micronutrientes and agar, with adjusted pH at 5,7. A month and for the multiplication phase it was cut in four parts the explante placing it in a half suplementado with high citoquininas concentration allowing the proliferation of lateral yolks, those that were separate to the two months, and placed in a means of cultivation that allowed the regeneration of complete plants; 30 days later the plants presented an appropriate radical system and foliage. In this phase he took the data of the variables in study. A factorial arrangement was used A x B, in a Design Completely Randomizado, where A = three varieties, B = three combinations of hormones, four replicas for treatment totalling 48 experimental units, the witness took citoquinina used in the multiplication phase, the test of Duncan was applied. The variety Williams with 4,79 cm of height was that of more average; for the factor hormones the best average with 4,25 cm was AIA, the lowest it was the witness with 3,53 cm. In number of roots, to the 30 days the best average was of 5,19 roots for the variety Cavendish Giant, followed Yaffa with 4,88 roots. For the hormones to the 30 days the best average 6,33 roots with 3 mg/l of ANA. For the longitude of roots the variety Williams obtained the best average with 5,30 cm; and with an average of 5,22 cm the hormone AIA with dose of 5 mg/l. The best weight of roots was for Cavendish Giant with 0,48 g; while for the hormones the ANA with 3 mg/l 0,46 g of roots obtained for plant.